2022
DOI: 10.1089/aut.2021.0083
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Differences in Psychiatric and Medical Diagnoses Among Autistic Adults

Abstract: Background: Racial/ethnic disparities in access to diagnostic services are pervasive for autistic children. However, a few studies have examined racial/ethnic health disparities among autistic adults, who commonly experience higher rates of health conditions than non-autistic adults. We aimed at examining the intersection of autism and race/ethnicity in association with psychiatric and medical diagnoses. Methods: The study population included adult members of Kaiser Per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 83 publications
0
1
0
Order By: Relevance
“…Further, those who are employed are more likely to have access to private health insurance. In fact, one study found a higher percentage of Latino adults with ASD were using public health insurance compared to non-Latino adults with ASD (Ames et al, 2022). The present study also found that Latinos with a first-time diagnosis of ASD did not significantly differ from White individuals with a first-time diagnosis of ASD across measures symptoms of ASD symptoms and distress.…”
Section: Discussionsupporting
confidence: 42%
“…Further, those who are employed are more likely to have access to private health insurance. In fact, one study found a higher percentage of Latino adults with ASD were using public health insurance compared to non-Latino adults with ASD (Ames et al, 2022). The present study also found that Latinos with a first-time diagnosis of ASD did not significantly differ from White individuals with a first-time diagnosis of ASD across measures symptoms of ASD symptoms and distress.…”
Section: Discussionsupporting
confidence: 42%
“…As previously mentioned, much of the current literature focuses on studying social identities, autistic traits, mental health, and camouflaging in separate studies. Across these studies, research has demonstrated that (1) social identity influences how autistic people view themselves and how others view them [e.g., ( 79 )], (2) social exclusion can lead to poor mental health outcomes [e.g., ( 93 )], (3) people with other marginalized identities have greater mental health concerns [e.g., ( 129 )], (4) camouflaging to fit in can be physically and emotionally taxing [e.g., ( 11 )], and (5) autistic people from other historically marginalized groups experience health disparities [e.g., ( 130 133 )]. Future research is needed to integrate these areas; such research can account for these complex theories by utilizing more advanced statistical approaches like structural modeling and implementing person-centered approaches like mixed methods research.…”
Section: Discussionmentioning
confidence: 99%
“…In a survey completed Wood and Happé (2020), results indicate that autistic students benefit from autistic educators as they serve as a role model and advocate. In a review of autistic teachers lived experiences, StEvens (2022) found teachers with disabilities foster inclusion and can counteract deficit narratives toward disability, which can be useful for neurotypical and autistic students. Further research could delve into the interaction between autistic educators and autistic students to see how communication and collaboration would be impacted.…”
Section: Working With Teachersmentioning
confidence: 99%